(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2017)
Arsenic is a metalloid that can be toxic to humans and other living organisms, occurs naturally and anthropogenic ally throughout the world at varying concentrations, including concentrations of concern in soil or groundwater. Presently, in Bihar (India) 16 districts are affected with arsenic poisoning in ground water causing lots of health hazards among the population and presently there is no solution for them. This arsenic intoxication has caused lots of problems related to kidney. The present study investigated the restorative effect Cadamba fruit extract on arsenic trioxide induced nephrotoxicity in mice. Arsenic trioxide (4 mgkgday b.wt) was administered to produce nephrotoxicity in rats followed by administration of Cadamba fruit extract (100 mgkgday p.o. 80 days) to attenuate the arsenic mediated nephro-toxicity. The kidney function tests were assayed and were found with elevated levels of urea, uric acid, and creatinine. Furthermore, their free radical assessment like lipid peroxidation levels were assayed which was found significantly high. Moreover the histopathological evaluations of kidney showed severe changes in mice treated with arsenic trioxide. But, after administration of aqueous extract of Cadamba fruit extract, it caused significant restoration in serum levels of urea, uric acid, creatinine, and lipid peroxidation levels and also in histological changes. Thus, it is evident from study that Cadamba fruit extract possesses antidote and acts effectively against arsenic induced nephrotoxicity.